2017
DOI: 10.1080/1059924x.2017.1317684
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism Signs and Symptoms in Agricultural Pesticide Handlers in Washington State

Abstract: Objectives Examine associations between pesticide exposure and signs or symptoms of parkinsonism. Methods Prior to the 2014 pesticide spray season we examined 38 active pesticide handlers age 35-65 (median 43.5) who participated in the State of Washington's cholinesterase monitoring program in the Yakima Valley, where cholinesterase-inhibiting insecticides are applied in fruit orchards. A movement disorders specialist assessed the workers using the Unified Parkinson's Disease Rating Scale (UPDRS) motor subsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Barriers to the use of this important preventive measure include low education levels, insufficient understanding of the importance of PPE and a lack of training, in addition to the high costs of specialized equipment. 5 , 6 , 10 A study performed in Ethiopia found that 42% of agricultural workers had never used PPE. 40 Ghafari et al 3 reported that 68% of rural workers in Iran did not use any form of PPE during pesticide application, while Zhang et al 38 , in China, reported that only 13.4% of farmers used PPE when handling pesticides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Barriers to the use of this important preventive measure include low education levels, insufficient understanding of the importance of PPE and a lack of training, in addition to the high costs of specialized equipment. 5 , 6 , 10 A study performed in Ethiopia found that 42% of agricultural workers had never used PPE. 40 Ghafari et al 3 reported that 68% of rural workers in Iran did not use any form of PPE during pesticide application, while Zhang et al 38 , in China, reported that only 13.4% of farmers used PPE when handling pesticides.…”
Section: Resultsmentioning
confidence: 99%
“…The association between pesticide use and Parkinson’s disease was investigated by Nielsen et al 10 in a study conducted in Washington, D.C, in the United States. Clinical and laboratory examinations performed before and after the period of exposure revealed little to no association between pesticide use and the development of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…When trying to assess cholinesterase changes due to chemical exposure, it is standard to take pre-and post-spraying samples to ascertain measurement alterations before and after exposure to pesticides. 18,[33][34][35][36][37] The Washington Farmers Study uses a definition of 20% cholinesterase depression to be clinically significant cholinesterase depression and is often used as the golden standard for many study looking at cholinesterase depression in farmworkers. 37 The Washington Cholinesterase Monitoring Program takes one baseline sample prior to spraying and one follow-up sample taken at one or more follow-up visits after a suspected exposure to organophosphates.…”
Section: Health Biomarkers and Symptomsmentioning
confidence: 99%
“…Indeed, several reports suggest lack of an association between chemical exposure and PD development. [11][12][13][14] As will be discussed in the ensuing section, these findings are attributed to several factors involving exposure route, period (acute/chronic), and the relationship of chemical-induced neurotoxicity leading to development of disease. MPTP is highly lipophilic compound that is converted into active metabolite 1-methyl-4-phenylpyridinium (MPP+) by monoamine oxidase B to be taken up by the dopamine transporters (DATs).…”
Section: -4mentioning
confidence: 99%